Algorithms of the popular Social Media platforms : opportunities in the cosmetic industry - Hakobyan, Irena (2023)
This master thesis aims to analyse the algorithms of the social media platforms and to study how those can be used to promote cosmetic products in Europe. To achieve the thesis goal, a detailed literature and article review was conducted. The essential finding from this review was the two most famous social media platforms listed per each country. In addition to this, two prominent cosmetic brands in the area of study were listed and their social media strategies were discussed. Based on the results, a set of procedures on how to benefit from the social media algorithms and promote cosmetic products was recommended. The central thesis output is a set of recommendations for the people who are planning to enter the cosmetic market in European countries or cosmetic industry entrepreneurs themselves